Assessment of Sharpe Model Suitability in Volatile Market Conditions - Kamila BEDNARZ-OKRZYŃSKA (Communications of International Proceedings, 2021)
The paper focuses on the determinant of economic growth – the stock market conditions and selected measures of sensitivity that reflect the impact of risk factors on return on investment. The main objective of the paper was to assess the Sharpe model suitability in volatile stock market conditions. The author sought to determine whether stock market conditions affect the value of β coefficient. The empirical study covered daily returns of WIG20 index companies achieved from October 4, 2001 to August 30, 2017. Within this time frame, four bull market periods and three bear market periods were distinguished. The analysis covered companies included in the WIG20 index in each of the analysed periods of bull market or bear market. A high amplitude of fluctuations in the value of β coefficient for a particular company was found to depend on the stock market conditions in a given period. However, there was no correlation observed between the value of β coefficient and the type of market trends: bullish or bearish.
Keywords: Economy; Stock Exchange; Risk; Market Conditions.